Plural Factors That Can Reshape Our Thinking - Bathurst, Ralph (Organizational Aesthetics, 2014)
As I write this editorial, we are entering the assessment season in our academic year here in Aotearoa New Zealand. No doubt we remember our own student years, during finals, experiencing anxiety, and perhaps fear of those questions for which we have not prepared. Now, as an instructor, on the other side of the academic divide, I find my anxiety has shifted from fear of the unknown, to doubt about what students have or have not discovered during their time with me in my class. The questions for me now are: "What did I teach and what did they learn?" And indeed, did my teaching and their learning in some ways coincide?